Socialization of emotions in school-age children with mental disorders: understanding of emotions an emotiogenic situations - Zhavnerko, Anastasiya P. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Features of emotional sphere is one of the most pronounced specific characteristics of the formation of the psyche of children with mental retardation. Emotions play an important role in communication between a child with a delay of mental development and the people around him. The article presents the results of a study features of emotions of children with mental retardation, emotional understanding of objectivity and emotional expression in the context of emotiogenic situation. Features described the emotional sphere of children, with mental retardation and with normal development allow us to make assumptions about the quality characteristics of the structure of mental disorders that are specific to mental retardation in children.